Modeling Risk Reduction in Agriculture Associated with Dangerous Agrometeorological Phenomena - Ashabokov, B A; Fedchenko, L M; Tashilova, A A; Shapovalov, A V; Khavtsukov, A Kh; Balkarova, S B (KnE Life Sciences, 2019)
The paper discusses possible approaches to reduce the risks associated with dangerous weather conditions. More specifically, the article considers the problem of reducing agricultural losses from such dangerous agrometeorological phenomena as hailstorm and drought. Within the framework of the decision-making theory, the formulation of the problem of reducing the losses of a considering industry from these phenomena is proposed – the objective is making decisions under risk. The features of the information support of this problem and the main tasks arising in the way of its practical use are discussed. The results of calculations that are carried out to analyze the effectiveness of the proposed method are given. The results of the calculations showed that the method is quite effective and can be used to reduce agricultural losses from hail.